Glabrimycetoporus amoenus, a new tachyporine genus and species of Mesozoic Staphylinidae (Coleoptera) from Liaoning, China - Yue, Yanli; Zhao, Yunyun; Ren, Dong (Zootaxa, 2009)
A new genus and species of well-preserved fossil Staphylinidae is described and illustrated. Glabrimycetoporus amoenus Yue, Zhao & Ren, gen. et sp. nov. is assigned to the tribe Mycetoporini in the subfamily Tachyporinae based on the following characters: head more or less inserted into prothorox, the tenth abdominal tergite broad and oblong; antennal insertions exposed and located anterior to a line drawn between anterior edges of eyes; body strongly tapered to the narrow head and abdominal apex. The specimen was discovered in the Upper Jurassic–Lower Cretaceous Yixian Formation of Beipiao City, Liaoning Province, NE China.